Targeting OXPHOS and the electron transport chain in cancer; Molecular and therapeutic implications. (November 2022) - Greene, John; Segaran, Ashvina; Lord, Simon
Abstract: Oxidative phosphorylation (OXPHOS) takes place in mitochondria and is the process whereby cells use carbon fuels and oxygen to generate ATP. Formerly OXPHOS was thought to be reduced in tumours and that glycolysis was the critical pathway for generation of ATP but it is now clear that OXPHOS, at least in many tumour types, plays a critical role in delivering the bioenergetic and macromolecular anabolic requirements of cancer cells. There is now great interest in targeting the OXPHOS and the electron transport chain for cancer therapy and in this review article we describe current therapeutic approaches and challenges.